Pulmonary Artery and Pulmonic Valve Vegetations in a Young Pregnant Filipino with Patent Ductus Arteriosus - Valerie R. Ramiro; Jezreel L. Taquiso; Stephanie Martha O. Obillos; Charlene F. Agustin; Jose Donato A. Magno; Eric Oliver D. Sison (Case Reports in Cardiology)
Background. Infective endocarditis (IE) involving the pulmonic valve and/or the pulmonary artery is rare. An unrepaired patent ductus arteriosus (PDA) is a risk factor for IE. A previous IE is also a risk factor that predisposes to IE recurrence. Discriminating between IE recurrence and a persistence of a vegetation from a previously treated IE can be difficult. We present the case of a 19-year-old primigravid with an unrepaired PDA and a history of IE treated 7 years prior, with positive blood cultures and vegetations on the pulmonic valve and pulmonary artery seen on transthoracic echocardiogram (TTE). Methods and Results. On TTE, a small-sized PDA with a Qp : Qs of 1.18 and vegetations on the pulmonic valve and pulmonary artery were documented. Despite the paucity of symptoms, she was empirically treated as culture-negative IE and given 2 weeks of ceftriaxone. Repeat TTE done after 2 weeks only showed a slight decrease in the vegetation size. Due to the paucity of symptoms of infection, lack of growth of the vegetation, and absence of embolic events, the vegetations were deemed to be persistent remnants from the previous IE rather than a recurrent IE. She was advised surgical PDA closure and harvest of vegetations after delivery, but the patient did not consent. The rest of her perinatal course was uneventful. Conclusion. Persistence of vegetations despite successful medical treatment occurs in some cases and has not been reported to be associated with increased morbidity. Therefore, a follow-up of IE after treatment should be guided by the clinical course and response to therapy as well as the echocardiographic morphology of vegetations over time.